COC Knipselkrant. - Nederlandse Vereniging tot Integratie van Homoseksualiteit COC ([S.l.] : NVIH COC, 1978)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijks
Redactie : s.l.
Nederlands
Periodiek